A Law Made by Places? An Investigation of the Objects and Normativity of the Cartographic Depictions - Mancin, Francesco (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The purpose of this contribution is to shed light on some dimensions of cartographic depictions, seen as normative drawings, that have so far been little explored: the peculiarity of topographic and cartographic representations and the way in which these representations are constructed. After introducing an operational definition of “map” and focusing attention on some essential characteristics, I analyse the surveying practices that depend on geodetic vertices, so called “fiducial points”, boundary stones and mesoscopic discontinuities. Subsequently, I try to highlight the problems related to the social ontology of topographic points and topographic maps, according to the lenses of weak realism and weak textualism. I state that mapping is a form of expression that is non-verbal but consistent with John R. Searle’s definition of language, based also on the materialization of topographic points in space. Finally, I raise three open questions about the relationship between topographic representations and constitutive rules. Parole chiave: Cartographic depictions; Normative drawings; Cadastrial maps; Constitutive rules; Documentality Indice: 1. Le rappresentazioni dello spazio topografico – 2. Quali punti? E per quali mappe? – 2.1 Vertici geodetici – 2.2 Punti fiduciali – 2.3 Cippi di confine – 2.4 Oggetti mesoscopici che possono assumere la funzione di cippo o punto notevole – 3. Mappe e ontologia sociale – 4. Normatività topografica – 4.1 Governo del territorio e regole costitutive – 4.2 Punti topografici come regole anankastiche? – 4.3 Cippi come regole athetiche non verbali? – Riferimenti bibliografici